PROFESSIONAL TRAINING OF FUTURE AGRICULTURAL SPECIALISTS FOR THE POST-WAR RECONSTRUCTION OF UKRAINE (Innovative professional education, 2024)
The highlights the environmental consequences of Russia’s armed aggression: soil destruction, chemical and radiological degradation processes, etc. The main international and domestic normative documents in the environmental sphere are outlined, where it is conceptually proven that post-war reconstruction and restorationshould take place according to the principle of «rebuild ecologically and better than it was». The main tasks of environmental education in the preparation of future specialists in the agricultural sector for the post-war reconstruction and restoration of Ukraine are also defined.
Keywords: ecology, professional education, specialists in the agricultural sector, «green» competences, eco-oriented pedagogical technologies.